On the construction of gravimetric geoid model on the Lviv region area - Zablotskyi, F.; Maksymchuk, V.; Dzhuman, B. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2022)
Baltic Height System 1977, currently used in Ukraine, the starting point of which is the zero of the Kronstadttide-gauge, isobsoletedue to the great distance from the zero-point of the reference height and the difficulty of adapting satellite methods of geodesy. For the successful modernization of the height system of Ukraine, it is necessary to integrate it into the United European Leveling Network (UELN). For the full functioning of any modern height system, namely to determine the gravity-depend heights by satellite methods, it is necessary to operate with a high-precision geoid model. Therefore, an important task is construction of a high-precision regional model of the geoid on the territory of our state. The rear many methods of constructing a model of the regional Earth’s gravitational field, including the geoid model, each of which has its advantages and disadvantages. The purpose of this article is to test the STHA-method for calculating the model of the regional gravitational field, in particular the gravimetric model of the geoid, on the territory of Lviv region and to assess its accuracy. Free air gravity anomalies ∆g from WGM2012 provided by the International Gravimetric Bureau (BGI) were used as initial data. The gravimetric STHA-model of the geoid was calculated with in the procedure «Remove-Compute-Restore» up to 8 degrees/order. To assess the accuracy of the model, it was compared with 213 points of GNSS leveling, as well as with the model EGM2008 up to 360 degrees/order. There are always differences between geometric and gravimetric geoid models duet or and ommeasurement errors, in consistencies in datums, different geodynamic effects etc. Respectively the parameters of the transition between gravimetric and geometric models of the geoid on the territory of Lviv region were also found. The proposed method can be used to build a high-precision model of the geoid for the entire territory of Ukraine with its subsequent coordination with the model of the European geoid EGG2015.